Near- and far-field dispersal modelling of organic waste from Atlantic salmon aquaculture in fjord systems. (21st March 2016) - Bannister, Raymond J.; Johnsen, Ingrid A.; Hansen, Pia K.; Kutti, Tina; Asplin, Lars
Abstract: The ability to achieve environmentally sustainable Atlantic salmon aquaculture in coastal fjord ecosystems is currently constrained by our limited knowledge of the regional interactions and fate of organic effluents on benthic ecosystems. A first step in addressing this limitation is to establish predictive modelling tools to better understand local and regional dispersion of organic effluents in the wider ecosystem. By combining settling velocity of faecal waste from different sizes of Atlantic salmon, a three-dimensional hydrodynamic model coupled with a particle tracking model and farm management data, this study presents a first-generation generic near- and far-field effluent dispersion model to predict the spread of particulate organic waste into fjord ecosystems. Simulations predict that >75% of organic effluents are dispersed to near-field sites (<500 m from the release point), while a small proportion of particulate organic effluents (up to 2.7%) are dispersed to far-field sites (>2 km). These simulations indicate that organic effluents from fish farms may be dispersed over large areas of fjord systems. The input of measured "mass fractions" settling velocities of faecal waste from different sizes of Atlantic salmon ensured that modelled predictions of near and far-field dispersion of organic material over a production cycle were in the range of observed POM fluxes.